ORGANIC GEOCHEMISTRY OF MIDDLE MIOCENE (BADENIAN – SARMATIAN) SOURCE ROCKS AND MATURATION MODELLING IN THE POLISH AND UKRAINIAN SECTORS OF THE EXTERNAL CARPATHIAN FOREDEEP. (20th June 2020) - Kosakowski, P.; Machowski, G.; Kowalski, A.; Koltun, Y. V.; Zakrzewski, A.; Sowiżdżał, A.; Stadtmuller, M.
Abstract : The Carpathian Foredeep to the north and NE of the Carpathian orogenic belt in SE Poland and NW Ukraine is divided into internal and external sectors. In the narrow internal foredeep, Lower and Middle Miocene shales, sandstones and interbedded evaporites are tightly folded. By contrast the external foredeep is characterized by the presence of a thick, unfolded Middle Miocene molasse succession. This ranges in thickness from a few hundred metres in the north of the external foredeep to >5000 m in the south, near the Carpathian thrust front. Middle Miocene sandstones in the external foredeep form a major reservoir for biogenic gas at fields in Poland and Ukraine. The Middle Miocene molasse succession in the external Carpathian Foredeep also contains organic‐rich intervals which have source rock potential. For this paper, core samples (n = 670) of Badenian and Sarmatian mudstones from 43 boreholes in the Polish sector of the external foredeep were analysed to investigate their organic geochemistry and hydrocarbon potential. Results show that the samples analysed in general have low to fair (but locally high) total organic carbon (TOC) contents which range up 4.6 wt.% although the average is only 0.7 wt.%. Rock‐Eval (S1 +S2 ) values are poor to fair and the hydrogen index is also low with a mean value of less than 100 mg/g TOC. The samples analysed are dominated by gas‐prone Type III kerogen and this is consistent with previous studies of time‐equivalent samples from the Ukrainian part of the external foredeep. The organic matter is in general thermally immature and is interpreted to have been deposited in anoxic and/or sub‐oxic conditions. However in the Polish part of the external foredeep, thermal maturities may locally reach the initial phase of the oil window where the Middle Miocene source rocks have been buried deeply beneath the Carpathian thrust front. The burial history and thermal evolution of the Middle Miocene succession were reconstructed by means of 1‐D modelling at nine boreholes located in both the Polish and Ukrainian parts of the external Carpathian foredeep. The modelling indicated that Middle Miocene source rocks have only entered the initial phase of the oil window locally where they are buried beneath the flysch nappes of the Carpathian foldbelt. At these locations the generation of thermogenic gas may have begun at depths of more than 3 km. However, Middle Miocene source rocks are still immature at depths of >4000 m in some boreholes in the Ukrainian part of the study area. The absence of accumulations of thermogenic natural gas is consistent with the observed low levels of source rock maturity.